Электоральные революции как фактор политической модернизации: опыт Чехии и Словакии - Башмаков, Димитрий С. (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
This paper discusses the transformation process of political systems in the Czech Republic and in Slovakia following the velvet revolution; the significance of civic society in the self-formation of political orientations and institutions via electoral revolutions is also considered.